The relationship between job stress and dyslipidemia. Issue 2 (March 2013) - Catalina-Romero, C.; Calvo, E.; Sánchez-Chaparro, M. A.; Valdivielso, P.; Sainz, J. C.; Cabrera, M.; González-Quintela, A.; Román, J.; ,
Aims: To investigate whether there is an association between job stress, lipid profile and dyslipidemia diagnosis. Methods: This study used a questionnaire to evaluate job stress and lifestyle variables in 91, 593 workers undergoing periodic checkups. Serum lipid levels were measured in all cases. Results: The prevalence of job stress was 8.7% (95% CI, 8.5–8.8%). In bivariate analyses, job stress was significantly associated with previous dyslipidemia diagnosis ( p < 0.001), lipid-lowering therapy ( p < 0.001), and altered total-cholesterol ( p = 0.001), HDL-cholesterol ( p < 0.001) and LDL-cholesterol levels ( p = 0.025). After adjusting for potential confounding variables, job stress was still associated with current dyslipidemia diagnosis (OR = 1.10; 95% CI, 1.04–1.17), high LDL-cholesterol (OR = 1.14; 95% CI, 1.05–1.23), low HDL-cholesterol (OR 1.08; 95% CI, 1.01–1.15), high total cholesterol/HDL-cholesterol ratio (OR 1.13; 95% CI, 1.05–1.23) and high LDL-cholesterol/HDL-cholesterol ratio (OR 1.11; 95% CI, 1.04–1.19). Conclusion: These results support the hypothesis of an association between job stress and lipid disturbances.